(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce a new operator based on the Sălăgean \( q \)-differential approach to define a new class of analytic functions. Using this operator, we obtain estimates for the first two coefficients in the Taylor series, \( |a_2| \) and \( |a_3| \). A significant part of the study focuses on the Fekete–Szegő inequalities for the function classes \( M_σ,q,Σ^ζ,m(, κ, α) \) and \( M_σ,q,Σ^ζ,m(γ,, κ) \). Through our analysis, we derive several important results, including some special cases that we present in this paper as Corollaries.